Good is the new cool guide to meaningful marketing how brands can win with conscious consumers - Aziz, Afdhel; Jones, Bobby (John Wiley & Sons, Inc., 2025)
"Today it is no longer enough for a brand to just be good'; it must also be cool'. Modern customers are demanding more social consciousness from the brands that they buy but also want to make sure it's balanced out by the right design, the right aesthetic, the right story told in an authentic and meaningful way. Equal parts self-help, how-to, and business journalism, this book aims to inspire others to be better marketers and citizens by balancing profit and the needs of their customers and communities, all while still innovating and harnessing the force of popular culture. "This book will revolutionize how companies position themselves and their brands, exploring a new purpose-driven business model and the millennial pioneers driving it to entrepreneurial success. Aziz and Jones' bold manifesto is provocative, whip-smart, and with streetwise style this book takes aim at conventional marketing, posing the questions few have had the vision and courage to ask If the system is broken, how can we fix it? Rather than sinking money into advertising, why not create a new model, in which great marketing benefits people and planet"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on March 07, 2025)
Keywords: Marketing -- Social aspects; Marketing -- Moral and ethical aspects; Branding (Marketing) -- Social aspects; Branding (Marketing) -- Moral and ethical aspects; Social responsibility of business; Consumption (Economics) -- Moral and ethical aspects; Consumers -- Attitudes; Marketing; Aspect social; Marketing; Aspect moral; Stratégie de marque; Aspect social; Stratégie de marque; Aspect moral; Entreprises; Responsabilité sociale; Société de consommation; Aspect moral; Consommateurs; Attitudes